Carotenoid production at various salinities in bacterium Rhodopseudomonas palustris - Reaksputi, Rapeeporn; Boonprab, Kangsadan; Tunkijjanukij, Suriyan; Salaenoi, Jintana (Agriculture and Natural Resources, 2019)
Rhodopseudomonas palustris, a phototrophic purple non-sulfur bacterium, is well known as a Gram negative, rod-shaped and motile cell. The effect of salinity on total carotenoid production and composition produced in R. palustris isolated from a paddy field was investigated. R. palustris was cultured for 30 d in Rhodopseudomonas medium, which was adjusted to four levels of salinity (0 parts per thousand, ppt; 10 ppt, 20 ppt and 30 ppt). The results revealed that mean (± SD) total carotenoid accumulation of R. palustris cultured in 0 ppt medium was faster at 9 d culture (46.30 ± 18.10 mg/L) than in 10 ppt medium at 21 d culture (57.27 ± 9.43 mg/L). At 30 d culture, the mean total carotenoid content at 0 ppt salinity (232.30 ± 52.53 mg/L) was similar with those produced at 10 ppt salinity (154.81 ± 41.47 mg/L, p > 0.05). The culture at 20 and 30 ppt salinity had minimal carotenoid content during the 30 d of the experiment. There was a fluctuating pattern of cell growth based on the dry cell weight for all salinity levels. Carotenoids and bacteriochlorophyll a were found in the extractions of R. palustris cultured in 0 ppt and 10 ppt salinity using spectrophotometry and thin-layer chromatography techniques. Interestingly, the results confirmed the synthesis of astaxanthin which was not commonly produced by this bacterium. online